Gray TiO2 Nanowires Synthesized by Aluminum‐Mediated Reduction and Their Excellent Photocatalytic Activity for Water Cleaning. Issue 40 (6th September 2013) - Yin, Hao; Lin, Tianquan; Yang, Chongyin; Wang, Zhou; Zhu, Guilian; Xu, Tao; Xie, Xiaoming; Huang, Fuqiang; Jiang, Mianheng
<x xml:space="preserve">Abstract</x> Not always black and white: Gray TiO2 nanowires with high photocatalytic activity have been successfully synthesized by aluminum‐mediated reduction in a two‐zone furnace. These wires, which possess a core (TiO2−x)/shell (TiO2) structure, exhibit visible‐light and even IR absorption with high photocatalytic activity (see figure), far exceeding that of commercial Degussa P25. They show high stability in air and water under solar‐light irradiation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>